Digital Writing Assistants in Business Writing: Students’ Perspectives and Writing Improvement Through Grammarly and Microsoft Word Editor - Yanik Sakinah; Hiqma Nur Agustina; Candrika Citra Sari; Rina Rachmawati (Bajang Institute, 2026)
The emergence of AI-based technology as a learning tool presents its challenges for English Foreign Language (EFL) students. Once AI offers convenience, it also affects the quality of students’ skills. This study aims to explore students’ perspectives on implementing two AI-based tools as writing correctors, Grammarly and Microsoft Word Editor (MWE). A mixed-method approach was employed to examine students’ experiences. Pre and post-tests with 19 students were conducted to collect quantitative data, while interviews were used to provide a qualitative in-depth perspective. The results reveal that students show improvements of 60%, 52%, 39% and 122% across four writing aspects: content, organization, appearance, and language used. On average, students achieve a score of 3.8 out of 4. Moreover, it reported that both tools were supporting their writing process. The findings provide valuable insights into understanding how the students can balance the benefits of AI-based tools with academic integrity.